Perlindungan Hak Konstitusional Melalui Pengaduan Konstitusional - Subiyanto, Achmad Edi (Mahkamah Konstitusi Republik Indonesia, 2011)
The idea of a constitutional complaint against the input (constitutional complaint) into the realm of the Constitutional Court is part of efforts to protect the rights of citizens protected by the Constitution of the Republic of Indonesia Year 1945. Protections that are stronger and more real to the constitutional rights of citizens in particular, and human rights in general, is one of the characteristics of the 1945 Constitution which has undergone a fundamental change in question. So, talking about the constitutional complaint in relation to the 1945 mean to talk about the 1945 Constitution which has undergone a fundamental change that. Therefore, an understanding of the occurrence of fundamental changes to the 1945 Constitution has become very important to explain that the constitutional complaint mechanisms and the need for the Constitutional Court is given authority to decide constitutional cases referred to the current complaint really has become a necessity.